Short-circuit fault management in DC electric ship propulsion system : protection requirements, review of existing technologies and future research trends - Satpathi, Kuntal (2019)
Ease of integration of the variable speed diesel generators resulting in substantial reduction of the fuel consumption is the key motivation for the development of the dc shipboard power system (SPS). One of the impediments to the widespread adoption of the dc SPS, however, has been the lack of comprehensive fault management strategies during the short-circuit faults. Such strategies comprise of fault detection, fault isolation, and reconfiguration of dc SPS. In the existing literature, all these aspects of fault management are dealt independently and mostly assuming ideal conditions. All the strategies are of utmost importance and it is needed to study them under a common framework which is the aim of this paper. This paper starts with a brief discussion on the characteristics of dc SPS along with recent modeling techniques. Subsequently, this paper describes the short-circuit fault studies, fault characteristics, and protection requirements. Finally, this paper outlines the working principle, advantages, and limitations of the fault detection, isolation, and reconfiguration strategies developed for the dc power system and analyzes their suitability to the dc SPS. This paper is concluded by identifying the future research trends needed for the development of the short-circuit fault management strategies of dc SPS for critical marine missions.